Assessment of thrombin-activatable fibrinolysis inhibitor levels in essential hypertension - Yıldız, Ayla; Okutur, Kerem; Eren, Nezaket (The European Research Journal, 2025)
Objectives: Most research in this field has highlighted the significance of the fibrinolytic system in essential hypertension, revealing anomalies within the coagulation and fibrinolytic pathways that contribute to a hypercoagulable condition. We aim to investigate thrombin-activatable fibrinolysis inhibitor (TAFI) levels in individuals diagnosed with high blood pressure. Methods: We compared 40 newly diagnosed cases of essential hypertension, who were not receiving antihypertensive medication, with 40 normotensive individuals as controls. Various parameters and TAFI levels were assessed in all subjects and compared between the groups. Additionally, hypertensive patients were classified based on whether they exhibited high or normal cholesterol levels (≥200 mg/dL). Results: The concentrations of TAFI were significantly higher in the hypertensive cohort compared to the normotensive counterparts (116.95±29.76 and 77.72±32.78 (ng/mL) , respectively; P